Stochastic modelling for network-based GPS positioning - Musa, Tajul A; Wang, Jinling; Rizos, Chris; Satirapod, Chalemchorn (Menay Pty Ltd, PO Box 1237, MILTON, QLD 4064 AUSTRALIA, 2003)
Over the past few years the concept of network-based positioning has been developed in support of longer baseline processing compared with 'traditional' single reference station positioning. In fact network-based positioning enables the generation of so-called ‘virtual measurements’, which can significantly improve positioning results. Even though the virtual measurements are generated from the stochastic network estimates, the error propagation into the user position solution has not been investigated in any detail. The aim is to understand how the unique stochastic properties of the network corrections propagate into the uncertainties of the estimated parameters. Test results indicate that by using the virtual measurements and considering the propagation of the network stochastic properties can provide reliable results, both in terms of ambiguity resolution and baseline component estimation.